2007
DOI: 10.1354/vp.44-2-218
|View full text |Cite
|
Sign up to set email alerts
|

FatalStreptococcus canisInfections in Intensively Housed Shelter Cats

Abstract: Abstract. Three independent, fatal outbreaks of Streptococcus canis infection occurred in a 2-year period in shelter cats. The outbreaks occurred in Northern California (Yolo County), Southern California (Kern County), and North Carolina (Guilford County). An estimation of the affected population is .150 cats among 3 affected shelters, with a mortality rate of up to 30%. Among 20 cats submitted for necropsy there were 2 distinct pathologic presentations. The first (shelters 1 and 2) was skin ulceration and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 9 publications
(17 reference statements)
2
44
0
6
Order By: Relevance
“…S. canis is the most common streptococcal species found in dog infections (11), being identified in cases of dermatitis, otitis externa, pneumonia, infective endocarditis, and adult septicemia (6,11,12). This species has also been implicated in fetal or neonatal septicemia, leading to abortion or neonatal death, respectively (2,11), and in both canine and feline necrotizing fasciitis and streptococcal toxic shock syndrome (13,14). S. canis may be transmitted between different animal species living in proximity (15) and has been responsible for outbreaks of clinical and subclinical mastitis with bacterial shedding in milk in cattle herds (16,17) and in pets living in shelters (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S. canis is the most common streptococcal species found in dog infections (11), being identified in cases of dermatitis, otitis externa, pneumonia, infective endocarditis, and adult septicemia (6,11,12). This species has also been implicated in fetal or neonatal septicemia, leading to abortion or neonatal death, respectively (2,11), and in both canine and feline necrotizing fasciitis and streptococcal toxic shock syndrome (13,14). S. canis may be transmitted between different animal species living in proximity (15) and has been responsible for outbreaks of clinical and subclinical mastitis with bacterial shedding in milk in cattle herds (16,17) and in pets living in shelters (14).…”
mentioning
confidence: 99%
“…This species has also been implicated in fetal or neonatal septicemia, leading to abortion or neonatal death, respectively (2,11), and in both canine and feline necrotizing fasciitis and streptococcal toxic shock syndrome (13,14). S. canis may be transmitted between different animal species living in proximity (15) and has been responsible for outbreaks of clinical and subclinical mastitis with bacterial shedding in milk in cattle herds (16,17) and in pets living in shelters (14). However, little is known about the genetic diversity of S. canis, namely, if there are clones particularly adapted to the different animal species.…”
mentioning
confidence: 99%
“…4,11,20 Only 1 potential virulence gene found in some human strains of S. pyogenes causing TSS (emm1.0 gene) was identified in 1 of 7 dogs that suffered from S. canis-associated TSS; in this study, no superantigens genes could be demonstrated. 9 As well, no superantigens have been detected to date in the strains of Streptococcus suis involved in the human outbreak of streptococcal TSS in China in 2005, which was clearly swine-associated.…”
mentioning
confidence: 50%
“…6 Severe streptococcal cellulitis associated with septicemia or toxic shock syndrome is rare, especially in veterinary medicine, but outbreaks due to Streptococcus canis have been described in dogs and cats, and Streptococcus agalactiae and Streptococcus pneumoniae were respectively cultured from a bottlenose dolphin and a kitten with cellulitis and septicemia. 9,11,20,21 Cellulitis has rarely been described in the bovine species. 1,12,13 In this species, it is often associated with Clostridium spp.…”
mentioning
confidence: 99%
“…Three dogs with STSS without necrotizing fasciitis (NF) died or were euthanatized within 48 h after admission, whereas 4 dogs with both STSS and NF survived after surgical debridement, supportive medical treatment, and antibiotic administration. In addition, 3 independent fatal outbreaks of GGS infection in shelter cats were reported within a 2-year period (2). The earlier outbreaks, in shelters 1 and 2, manifested as skin ulcerations and chronic respiratory infections that progressed to necrotizing sinusitis and meningitis.…”
Section: Introductionmentioning
confidence: 99%